A reassessment of the role of oxygen scavenging enzymes in the emergence of metronidazole resistance in trichomonads. (August 2021) - Gehl, Virág; Paunkov, Ana; Leitsch, David
Abstract: Trichomonads are an order of parasitic protists which infect a wide range of hosts. The human parasite Trichomonas vaginalis and the bovine parasite Tritrichomonas foetus which also infects cats and swine are of considerable medical and veterinary importance, respectively. Since trichomonads are microaerophiles/anaerobes they are susceptible to 5-nitroimidazoles such as metronidazole. 5-nitroimidazoles are exclusively toxic to microaerophilic/anaerobic organisms because reduction, i.e. activation, of the drug can only occur in a highly reductive environment. 5-nitroimidazoles have remained a reliable treatment option throughout the last decades but drug resistance can be a problem. Clinical resistance to 5-nitroimidazoles has been studied in more detail in T . vaginalis and has been ascribed to defective oxygen scavenging mechanisms which lead to higher intracellular oxygen concentrations and, consequently, to less drug being reduced. Two enzymes, flavin reductase (FR) and NADH oxidase have been suggested to be the major oxygen scavenging enzymes in T . vaginalis . The loss, or at least an impairment of FR which reduces oxygen to hydrogen peroxide, has been proposed as the central mechanism that enables the emergence of 5-nitroimidazole resistance. In this study we explored if T . foetus also encodes a homolog of FR and if it is, likewise, involved in resistance. T. foetus was indeed found to express a FR but it was only weakly active as compared to the T . vaginalis homolog. Further, activity of FR in T . foetus was unchanged in metronidazole-resistant cell lines, ruling out that it has a role in metronidazole resistance. Finally, we measured oxygen scavenging rates in metronidazole-sensitive and –resistant cell lines and found that NADH oxidase and FR are not the major oxygen scavenging enzymes in trichomonads and that oxygen scavenging is possibly a consequence, rather than a cause of metronidazole resistance. Graphical abstract: Image 1 Highlights: T. foetus encodes a flavin reductase (FR) like T. vaginalis but it is less active. FR is not downregulated in metronidazole-resistant T. foetus as in T. vaginalis. Flavin reductase and NADH oxidase are not the major oxygen scavenging enzymes. Defective oxygen scavenging is not necessarily a cause of metronidazole resistance.